Burkina Faso Jobs Diagnostic : Overview and Suggestions for a Strategic Framework for Jobs - Weber, Michael (World Bank, Washington, DC, 2018)
Over the recent past, Burkina Faso has registered solid economic growth and poverty levels have been lowered, suggesting that growth has been pro-poor. Yet, poverty remains widespread despite high levels of labor market participation and employment. In practice, life for many in the country remains a struggle, even when compared to equally challenging conditions elsewhere in the region. The overview report on the Jobs Diagnostic: Burkina Faso; provides a multi-sectoral analysis of the country's jobs challenges by looking at macro-economic conditions and trends, hindrances to labor demand, issues affecting jobs outcomes in agriculture and determinants of jobs outcomes in general. The report draws on recent household and enterprise surveys and provides regional comparisons that place the challenges in Burkina Faso in a wider context. It closes with preliminary policy recommendations for a future jobs strategy.